Eskatologiens udvikling hos den historiske Jesus - Theißen, Gerd (Dansk teologisk tidsskrift, 2009)
Resumé This article reviews Per Bilde’s Den historiske Jesus. Three theses of Bilde are discussed: (1) The “sign prophets” in the first century C.E. are the nearest analogies to Jesus, but we should make a difference between those before the Caligula-crisis, who have been interested in cult and conversion, and those after this crisis. (2) Jesus had a messianic consciousness, but participated in a mentality that says: Nobody can legitimately give oneself a new status he can only receive it from a superior. (3) There is a development from proclaiming God’s mercy to announcing God’s judgement, but the interpretation of Jesus’ death as atoning death seems to be a retrospective interpretation after Easter. We may therefore say: The main three theses are basically justified but theyshould be modified a little bit.